CLASSROOM MANAGEMENT STRUCTURES (Лучшие интеллектуальные исследования, 2025)
Abstract : A key component of good teaching and learning is efficient classroom management. It guarantees a classroom atmosphere, reduces disturbances, and cultivates a favorable teacher-student rapport. This article examines several classroom management systems, offers real-world examples, and highlights how crucial they are to fostering a positive and effective learning environment.